The Integrated Learning Model in Islamic Religious Education in ‎Junior High School - Al Khansa, Elsa; Pahrudin, Agus; Jatmiko, Agus; Sufian, Muhammad; Azad, Inamul (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
The integrated learning model in Islamic Religious Education at the junior high ‎school level seeks ‎to improve students' understanding of religious values and ‎engagement in learning‎. This study examines the application of the ‎integrated learning model in Islamic Religious Education at the junior high school ‎level, focusing on its impact on students' understanding of religious values and ‎engagement in the learning process. This study was conducted at Al Azhar 1 Junior ‎High School in Bandar Lampung. A descriptive qualitative approach was employed ‎to explore the implementation of the integrated learning model. Data were ‎collected through semi-structured interviews, observations, and document ‎analysis. The participants included teachers, students, the school principal, and the ‎vice principal. Analysis followed Miles and Huberman's ‎interactive ‎model, with data validity ensured through triangulation, offering an objective view ‎of ‎the model's effect on student engagement and understanding. Results showed that the integrated learning model effectively connects religious values with students' real-life contexts, enhancing their understanding and participation. Students became more active in discussions and felt motivated to apply religious values in their daily lives, mainly through themes like honesty, discipline, and cooperation presented in relatable scenarios. The study implies that the integrated learning model in Islamic Religious Education increases student engagement and supports positive character development. These findings provide valuable insights for designing a more engaging and impactful curriculum that aligns with the goals of Islamic Religious Education.